2017
DOI: 10.1080/0020739x.2017.1285060
|View full text |Cite
|
Sign up to set email alerts
|

Attitude toward mathematics among the students at Nazarbayev University Foundation Year Programme

Abstract: This article investigates the attitude toward mathematics among the students enrolled in the Foundation Year Programme at Nazarbayev University. The study is conducted quantitatively and an inventory developed by Tapia and Marsh II is adopted in this research. The inventory consists of 40 statements on the five-point Likert scale. Gender, specialization and final high school score in mathematics are collected. The number of valid returned questionnaires is 108. There are 55 males, 53 females, 73 Mathematical-P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 81 publications
3
15
0
2
Order By: Relevance
“…The finding of this study is consistent with the findings of Sirmaci (2010), which found that there was a significant relationship between the attitudes of the students towards mathematics and their performance in math. Moreover, this finding is also supported by that of Karjanto (2017), which found that there was a significant positive correlation between the achievement in math and the attitudes of the students. Be that as it may, there was no unique distinction in the frames of mind of the respondents towards science dependent on sexual orientation.…”
Section: Test Of Significant Relationshipsupporting
confidence: 69%
See 1 more Smart Citation
“…The finding of this study is consistent with the findings of Sirmaci (2010), which found that there was a significant relationship between the attitudes of the students towards mathematics and their performance in math. Moreover, this finding is also supported by that of Karjanto (2017), which found that there was a significant positive correlation between the achievement in math and the attitudes of the students. Be that as it may, there was no unique distinction in the frames of mind of the respondents towards science dependent on sexual orientation.…”
Section: Test Of Significant Relationshipsupporting
confidence: 69%
“…However, no significant gender difference was found in their attitudes. Karjanto (2017) investigated the attitudes of the 108 students in mathematics who are enrolled in Nazarbayev University using the Attitudes Towards Mathematics Inventory (ATMI) by Tapia and Marsh (2004). Results revealed that students have a positive attitude towards mathematics.…”
Section: Related Literaturementioning
confidence: 99%
“…As depicted by Caliskan, (2019) mathematical self-efficacy beliefs did not differ by gender. The result is aligned with the research finding of some previous researches (Farooq & Shah, 2008;Yasar, 2016;Kaur, 2017;Karjanto, 2017;Dowker, et al, 2019;Batool et al, 2020;Fernández-CĂ©zar et al, 2020;Zakaria, R. et al, (2020)). However the result contradicts that there were significant gender differences in students' attitudes towards learning mathematics in favor of male students (Dan'inna, 6;Soleymani & Rekabdar, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Walau bagaimanapun, kajian ini merupakan kajian korelasi yang mana keputusan kajian tidak boleh dikaitkan dengan sebab dan akibat. Dapatan ini adalah bertentangan dengan kajian-kajian lepas yang mendapati bahawa terdapat hubungan antara sikap pelajar dengan pencapaian matematik (Capuno et al, 2019;Damrongpanit, 2019;Karjanto, 2017;Kibrislionglu, 2015;Tanujaya et al 2017) Dalam kajian Kibrislionglu (2015), perbezaan dapatan kajian tersebut dengan dapatan kajian ini adalah disebabkan oleh faktor responden kajian yang mana responden yang terlibat adalah terdiri daripada pelajar yang mempunyai pencapaian matematik yang baik. Keadaan tersebut berbeza halnya dengan kajian ini yang mana kebanyakan responden yang terlibat dalam kajian ini adalah terdiri daripada kumpulan pelajar yang memiliki pencapaian yang kurang baik dalam matematik.…”
Section: Perbincangan Kajianunclassified